Ethics of Communication of Advocacy Cases - Stephanie Susanto*; Firman Kurniawan S (Universitas Syiah Kuala, 2023)
Freedom of speech and expression must be accompanied by ethics and sensitivity when a message is delivered. Otherwise, the purpose of delivering the message may fail-the presence of rejection and adverse reactions from people who read or receive messages. The tragedy at Kanjuruhan stadium can be seen from various aspects: communication ethics, especially in speaking, thinking, and behaving. Second, based on the spiral of silence theory, discourse debates give rise to a diversity of opinions that will eventually narrow down to a single phase of silence. Using Literature Review, this study will explain various things from the wealth of opinions circulating in the community through Twitter and online media from 01 October – 14 October 2022.